Study Of Pulmonary Function Tests In Type 2 Diabetic Patients: Correlation With Glycemic Status - DR.G.V.KULKARNI; DR.ANIL D.SURDI (International Journal of Pharma and Bio Sciences, 2015)
Diabetes is one of the leading causes of death worldwide. As lung is a target organ for diabetes type 1 and 2, in this cross-sectional study, we studied the pulmonary functions of 60 type 2 diabetic patients and 60 matched controls by spirometry. Blood sugar, fasting and post-prandial was measured in all subjects by oxidase-peroxidase method. We found a significant reduction in FVC, FEV1, MVV in diabetics compared to controls. A significant increase in FVC/FEV1% was seen in diabetics compared to controls. Blood sugar, correlated significantly & negatively with FVC, FEV1 and MVV, significantly and positively with FVC/FEV1% in diabetic subjects. Our results showed mainly the restrictive type of lung impairment in type 2 diabetes and significant impairment of lung function with increasing blood sugar levels. It is advisable that diabetic patients should undergo periodic spirometric check up to assess severity of lung function impairment and their glycemic control should be improved.